Constraints on Higgs boson production with large transverse momentum using H→bb[bar] decays in the ATLAS detector - Aad, Georges; Baltes, Lisa Marie; Bartels, Falk; Castillo, Florencia Luciana; Czurylo, Marta; Dittmeier, Sebastian; Dunford, Monica; Franchino, Silvia; Klassen, Martin; Krishnan, Anjali; Mkrtchyan, Tigran; Ott, Philipp; et al. (Physical review, 2022)
This paper reports constraints on Higgs boson production with transverse momentum above 1 TeV. The analyzed data from proton-proton collisions at a center-of-mass energy of 13 TeV were recorded with the ATLAS detector at the Large Hadron Collider from 2015 to 2018 and correspond to an integrated luminosity of 136 fb−1. Higgs bosons decaying into b¯b are reconstructed as single large-radius jets recoiling against a hadronic system and are identified by the experimental signature of two b-hadron decays. The experimental techniques are validated in the same kinematic regime using the Z→b¯b process. The 95% confidence-level upper limit on the cross section for Higgs boson production with transverse momentum above 450 GeV is 115 fb, and above 1 TeV it is 9.6 fb. The Standard Model cross section predictions for a Higgs boson with a mass of 125 GeV in the same kinematic regions are 18.4 fb and 0.13 fb, respectively.